1994
DOI: 10.1038/bjc.1994.159
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of p53 antibodies in sera of patients with lung carcinoma define immunodominant regions in the p53 protein

Abstract: Summary Antibodies specific for human p53 were analysed in sera of lung cancer patients. We detected p53 antibodies in the sera of 24% (10/42) of patients with lung carcinoma. The distribution was as follows: 4/9 small-cell lung carcinomas (SCLCs), 2/18 squamous cell lung carcinomas (SCCs), 2/10 adenocarcinomas (ADCs) and 2/5 large-cell lung carcinomas (LCCs). p53 antibodies were always present at the time of diagnosis and did not appear during progression of the disease. Using an original peptide-mapping proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
3
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 25 publications
4
54
3
1
Order By: Relevance
“…These antibodies recognize immunodominant epitopes localized in the amino-and, to a lesser extent, in the carboxy-terminus of human p53 (Lubin et al, 1993;Schlichtholz et al, 1994;Vennegoor et al, 1997). Antibodies specific for the central region are always poorly abundant or absent (Lubin et al, 1993).…”
mentioning
confidence: 99%
“…These antibodies recognize immunodominant epitopes localized in the amino-and, to a lesser extent, in the carboxy-terminus of human p53 (Lubin et al, 1993;Schlichtholz et al, 1994;Vennegoor et al, 1997). Antibodies specific for the central region are always poorly abundant or absent (Lubin et al, 1993).…”
mentioning
confidence: 99%
“…Studies have shown that 9-26% of patients with different carcinomas have mounted a humoral immune response (antibodies) to abnormal p53 protein (Caron de Fromental et al, 1987;Levine et al, 1991;Angelopoulou et al, 1994). Thus, anti-p53 antibodies may be a serological marker for malignancy.Recent studies have shown increased serum antibody levels against mutant p53 protein in patients with breast (Crawford et al, 1982;Davidoff et al, 1992;Schlichtholtz et al, 1992;Mudenda et al, 1994), lung (Winter et al, 1992;Schlichtholtz et al, 1994) and Immunohistochemical analysis of overexpression of p53 protein p53 protein overexpression was evaluated using an immunohistochemical method (Kressner et al, 1996). Briefly, DO-7 monoclonal antibody was used in combination with biotinylated horse antimouse IgG antibody as secondary antibody, followed by avidin-biotin blocking kit and ethyl carbazole substrate.…”
mentioning
confidence: 99%
“…Recent studies have shown increased serum antibody levels against mutant p53 protein in patients with breast (Crawford et al, 1982;Davidoff et al, 1992;Schlichtholtz et al, 1992;Mudenda et al, 1994), lung (Winter et al, 1992;Schlichtholtz et al, 1994) and colorectal cancer (Houbiers et al, 1995;Angelopoulou et al, 1997). Two of the studies in breast cancer patients have indicated that the occurrence of p53 antibodies may be a useful determinant with regard to poor prognosis (Schlichtholtz et al, 1992;Mudenda et al, 1994).…”
mentioning
confidence: 99%
“…In a lunc cancer series. Schlichtholz et al (1994) reported that anti-p53 antibodies were found in sera in 20.0% of patients with adenocarcinoma. [Schlichtholz et al 1994: Trivers et al 1996 as well as our own.…”
Section: Discussionmentioning
confidence: 99%
“…Schlichtholz et al (1994) reported that anti-p53 antibodies were found in sera in 20.0% of patients with adenocarcinoma. [Schlichtholz et al 1994: Trivers et al 1996 as well as our own. anti-p53 levels determined by ELISA are continuously plotted for :ancer patients and appear to be higher than those in normal control subjects.…”
Section: Discussionmentioning
confidence: 99%